Normal or Arthritic: Is 25-hydroxy Vitamin D status significant? - Bista, Krishna Bahadur; Lamichhane, PP; Regmi, SM; Naglla, A; Shrestha, S (Journal of Gandaki Medical College-Nepal, 2017)
Background: Vitamin D is required for proper skeletal development and function. However, the status of vitamin D in healthy subjects and those suffering from arthritis in Nepal is largely unknown. Objective: This study measured vitamin D level in healthy and arthritic individuals of Western Nepal. Methods: Vitamin D level in healthy and arthritic subjects were measured by using LIASION 25-hydroxy Vitamin D assay, a direct competitive chemiluminescence immunoassay (CLIA). Results: Our result suggested that most of the subjects, irrespective of age and disease condition, have subnormal/normal level of vitamin D (≥16ng/mL). Also, the data suggested that serum vitamin D level is significantly higher in males than in females. Moreover, the vitamin D level is higher in healthy individuals when compared with those suffering from arthritis. However, vitamin D level in normal subjects and arthritic patients could not be correlated. Conclusion: Vitamin D level is higher in normal subjects compared to arthritic individuals. However, the level could not be correlated suggesting need of a pilot study to determine vitamin D level and its association with arthritis in Nepalese. Journal of Gandaki Medical College Vol. 10, No. 1, 2017, Page: 21-24